Chromosomal-level reference genome of Chinese peacock butterfly (Papilio bianor) based on third-generation DNA sequencing and Hi-C analysis. Issue 11 (4th November 2019) - Lu, Sihan; Yang, Jie; Dai, Xuelei; Xie, Feiang; He, Jinwu; Dong, Zhiwei; Mao, Junlai; Liu, Guichun; Chang, Zhou; Zhao, Ruoping; Wan, Wenting; Zhang, Ru; et al.
Abstract: Background: Papilio bianor Cramer, 1777 (commonly known as the Chinese peacock butterfly) (Insecta, Lepidoptera, Papilionidae) is a widely distributed swallowtail butterfly with a wide number of geographic populations ranging from the southeast of Russia to China, Japan, India, Vietnam, Myanmar, and Thailand. Its wing color consists of both pigmentary colored scales (black, reddish) and structural colored scales (iridescent blue or green dust). A high-quality reference genome of P. bianor is an important foundation for investigating iridescent color evolution, phylogeography, and the evolution of swallowtail butterflies. Findings: We obtained a chromosome-level de novo genome assembly of the highly heterozygous P. bianor using long Pacific Biosciences sequencing reads and high-throughput chromosome conformation capture technology. The final assembly is 421.52 Mb on 30 chromosomes (29 autosomes and 1 Z sex chromosome) with 13.12 Mb scaffold N50. In total, 15, 375 protein-coding genes and 233.09 Mb of repetitive sequences were identified. Phylogenetic analyses indicated that P. bianor separated from a common ancestor of swallowtails ∼23.69–36.04 million years ago. Demographic history suggested that the population expansion of this species from the last interglacial period to the last glacial maximum possibly resulted from its decreased natural enemies and its adaptation to climate change during the glacial period. Conclusions: We present a high-quality chromosome-level reference genome of P. bianor using long-read single-molecule sequencing and Hi-C–based chromatin interaction maps. Our results lay the foundation for exploring the genetic basis of special biological features of P. bianor and also provide a useful data source for comparative genomics and phylogenomics among butterflies and moths.